Synthesis and characterization of doped Mg2Si0.4Sn0.6 thermoelectric material made in exclusion of glove box. (15th September 2022) - Howlader, Smita; Gupta, S.; Vasudevan, R.; Sachdev, K.
Abstract: The Mg2 X (X = Si and Sn) based alloys which are composed of abundant, non-toxic and inexpensive elements are promising mid-temperature thermoelectric (TE) materials. Herein, we report the synthesis of Mg2 Si0.4 Sn0.6 through high energy ball milling followed by hot pressing for thermoelectric application, where handling of the elemental powders was processed in the ambient laboratory conditions in the exclusion of the glove box. Mg2 Si0.4∼0.3 Sn0.6∼0.7 shows conduction band convergence which is a favorable feature for enhancing the zT in the n-type TE material, and dopants Bi, Sb and Al have been used for imparting the n-type conduction. To get enhanced p-type performance, heavier compositions are feasible and the same parent composition has been used for Ag as a dopant to provide p-type conductivity. The samples have been investigated for confirmation of phases and elements, electrical and thermoelectric transport properties using X-Ray Diffractometer, Hall effect measuring equipment, Semiconductor Device Analyzer, ZEM, and Laser Flash Analyzer. The Ag-doped sample showed comparatively better electrical properties owing to an additional p-type conductivity rendered by the antisite defects of Mg on Si (MgSi ). Further, its elemental and microstructural analysis were carried out by an X-ray Photoelectron Spectroscopy, Scanning Electron Microscope, and Transmission Electron Microscope, respectively. Highlights: Bi, Sb, Al and Ag doped Mg2 Si0.4 Sn0.6 were synthesised via ball milling and subsequent hot press. The handling and weighing of elemental powders and also the opening of the milling vials were done in ambient air. Extended milling has not been found helpful but only unfavourable by partially decomposing the standard cubic Mg2 Si0.4 Sn0.6 phase to hexagonal Mg2 Sn, making it even more difficult to obtain the band degeneracy.